Examining the Challenges and Strategies for Improving Cervical Cancer Screening in Nigeria - Gamde, Solomon Matthias; Omotola, Olatunde Sharon; Avwioro, Godwin O; Adisa, James O (International Journal of Human and Health Sciences (IJHHS), 2024)
Background: Cervical cancer is one of the most treatable cancers when detected early and managed. Unfortunately, the mortality rate is projected to surge in Nigeria. Objective: This review aims to provide updated information on challenges and strategies for improving cervical cancer screening in Nigeria. Methods: In this review, scientific papers published in electronic databases including PubMed, Scopus, and Google Scholar were retrieved using search themes such as “cervical cancer”, “risk factors”, and “preventive methods” were examined. Results: The true prevalence of cervical cancer is underestimate in Nigeria because most cases of cervical cancer are not documented. Lack of awareness, cultural barriers, poor infrastructure, unfavorable perception, shortage of supplies, lack of partner involvement, provider-related factors, poor monitoring, and evaluation system were the major barriers that hinder cervical cancer screening service in Nigeria. Conclusion: Lack of awareness, unfavorable perception, problems with health system structure and process, and cultural conditions were major barriers in Nigeria. Hence, packages of intervention is necessary create awareness, provide essential equipment, increase access to health facilities, and strengthening follow up system is indispensable for service improvement by the government and non-governmental organizations, world health organization inclusive. International Journal of Human and Health Sciences Vol. 08 No. 01 Jan’24 Page: 22-31